Pengembangan Media Pembelajaran Berbasis Multimedia pada Mata Kuliah Bakery - Ezi Anggraini; Anni Faridah; Reno Yelfi (Jurnal Pendidikan Teknologi Kejuruan, 2019)
Based on preliminary observations, the learning outcomes and creativity of IKK Department students who take the Bakery course are still low, it is estimated that the low learning outcomes are due to the limitations of existing learning resources or learning media, there are still deficiencies in the existing learning media. Therefore, designed and made a learning medium in the form of multimedia learning for Bakery courses. The purpose of this research was to develop the learning media based multimedia that valid, practice, and effective for bakery. This research used Research and Development (R&D) method, and 4D (four-D) model that develop by S. Thiagarajan and friends. There were four steps in 4D model, there were define, design, develop, dessiminate. The media was diesigned by using Macromedia Flash CS 6. The result of this research was that the learning media based multimedia were valid, practice, and effective to use as a learning media of bakery.